2005
DOI: 10.1007/s11263-005-6642-x
|View full text |Cite
|
Sign up to set email alerts
|

Image Parsing: Unifying Segmentation, Detection, and Recognition

Abstract: In this paper we present a Bayesian framework for parsing images into their constituent visual patterns. The parsing algorithm optimizes the posterior probability and outputs a scene representation in a "parsing graph", in a spirit similar to parsing sentences in speech and natural language. The algorithm constructs the parsing graph and re-configures it dynamically using a set of reversible Markov chain jumps. This computational framework integrates two popular inference approaches -generative (top-down) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
364
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(367 citation statements)
references
References 36 publications
3
364
0
Order By: Relevance
“…Compared with past computational modeling, previous models have used part-based object recognition (31)(32)(33) and combined BU with TD processing (18,19,(34)(35)(36). However, past models did not study or report results on part recognition, did not examine the limitations of feed-forward models for part recognition, and did not demonstrate the contribution of a fast TD process to part detection and localization.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with past computational modeling, previous models have used part-based object recognition (31)(32)(33) and combined BU with TD processing (18,19,(34)(35)(36). However, past models did not study or report results on part recognition, did not examine the limitations of feed-forward models for part recognition, and did not demonstrate the contribution of a fast TD process to part detection and localization.…”
Section: Discussionmentioning
confidence: 99%
“…The large diversity of image segment types has increased the urge to devise a unified segmentation approach. Tu et al [13] provided such a unified probabilistic framework, which enables to "plug-in" a wide variety of parametric models capturing different segment types. While their framework elegantly unifies these parametric models, it is restricted to a predefined set of segment types, and each specific object/segment type (e.g., faces, text, texture etc.)…”
Section: Fig 3 Notationsmentioning
confidence: 99%
“…Our work builds on top of [14], providing a general segment quality score and a corresponding image segmentation algorithm, which applies to a large diversity of segment types, and can be applied for various segmentation tasks. Although general, our unified segmentation framework does not require any pre-definition or modelling of segment types (in contrast to the unified framework of [13]). …”
Section: Basic Concept -"Segmentation By Composition"mentioning
confidence: 99%
“…As can be seen, the top-down segmentation is better than any of the bottom-up segmentations but still misses important details. In recent years, several authors have therefore suggested combining top-down and bottom-up segmentation [2,21,17,6]. Borenstein et al [2] choose among a discrete set of possible low-level segmentations by minimizing a cost function that includes a bias towards the top-down segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Borenstein et al [2] choose among a discrete set of possible low-level segmentations by minimizing a cost function that includes a bias towards the top-down segmentation. In the image parsing framework of Tu et al [17] object-specific detectors serve as a proposal distribution for a data-driven Monte-Carlo sampling over possible segmentations. In the OBJ-CUT algorithm [6] a layered pictorial structure is used to define a bias term for a graph-cuts energy minimization algorithm (the energy favors segmentation boundaries occurring at image discontinuities).…”
Section: Introductionmentioning
confidence: 99%